PENGEMBANGAN MEDIA TAKERANA BERBASIS GENIALLY BERBANTUAN LAGU UNTUK MENINGKATKAN HASIL BELAJAR MURID KELAS V - Aviana Zuhrotun Nabilah; Putri Yanuarita Sutikno (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The low learning outcomes of students on the diversity of Indonesian flora and fauna topic motivated the importance of utilizing contextual interactive learning media in elementary schools. This Research and Development study applying eight adapted Borg and Gall stages aimed to examine the feasibility, practicality, and effectiveness of song-assisted Genially-based TAKERANA media. Research subjects comprised 28 fifth-grade students at SD Negeri Tambakaji 03 divided into a small group (9 students) and a large group (19 students). Data were gathered using validation questionnaires, response sheets, and learning outcome tests (pretest-posttest). Data were statistically analyzed using paired sample t-tests and Normalized Gain (N-Gain) indices. Expert validation results confirmed media feasibility at 94 percent from media experts and 96 percent from subject matter experts (highly feasible). Media practicality achieved positive response rates of 90 percent from students and 98 percent from teachers (excellent). Paired sample t-test results revealed a significant difference (p < 0.001), with average N-Gain values of 0.6179 in the small group and 0.5160 in the large group (moderate category). The main conclusion confirms that song-assisted Genially-based TAKERANA media is highly feasible, practical, and effective in enhancing elementary science learning outcomes. ABSTRAK Rendahnya hasil belajar peserta didik pada materi keanekaragaman flora dan fauna Indonesia melatarbelakangi pentingnya penggunaan media pembelajaran interaktif yang kontekstual di sekolah dasar. Penelitian Research and Development (R&D) menggunakan delapan tahapan adaptasi Borg dan Gall ini bertujuan menguji kelayakan, kepraktisan, serta efektivitas media TAKERANA berbasis Genially berbantuan lagu. Subjek penelitian terdiri atas 28 peserta didik kelas V SD Negeri Tambakaji 03 yang terbagi ke dalam kelompok kecil (9 siswa) dan kelompok besar (19 siswa). Pengumpulan data menggunakan angket validasi, angket respon, dan tes hasil belajar (pretest-posttest). Data dianalisis secara statistik kuantitatif menggunakan uji paired sample t-test dan indeks Normalized Gain (N-Gain). Hasil validasi ahli mengonfirmasi kelayakan media sebesar 94 persen dari ahli media dan 96 persen dari ahli materi (sangat layak). Kepraktisan media mencapai respon positif 90 persen dari peserta didik dan 98 persen dari guru (sangat baik). Hasil uji paired sample t-test menunjukkan perbedaan signifikan (p<0,001), dengan rata-rata nilai N-Gain sebesar 0,6179 pada kelompok kecil dan 0,5160 pada kelompok besar (kategori sedang). Simpulan utama menegaskan bahwa media TAKERANA berbasis Genially berbantuan lagu terbukti sangat layak, praktis, serta efektif meningkatkan hasil belajar IPAS peserta didik.